Mechanism of the Oxidation of 3, 3′, 5, 5′‐Tetramethylbenzidine Catalyzed by Peroxidase‐Like Pt Nanoparticles Immobilized in Spherical Polyelectrolyte Brushes: A Kinetic Study. Issue 5 (3rd February 2020) - Gu, Sasa; Risse, Sebastian; Lu, Yan; Ballauff, Matthias
Abstract: Experimental and kinetic modelling studies are presented to investigate the mechanism of 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) oxidation by hydrogen peroxide (H2 O2 ) catalyzed by peroxidase‐like Pt nanoparticles immobilized in spherical polyelectrolyte brushes (SPB−Pt). Due to the high stability of SPB−Pt colloidal, this reaction can be monitored precisely in situ by UV/VIS spectroscopy. The time‐dependent concentration of the blue‐colored oxidation product of TMB expressed by different kinetic models was used to simulate the experimental data by a genetic fitting algorithm. After falsifying the models with abundant experimental data, it is found that both H2 O2 and TMB adsorb on the surface of Pt nanoparticles to react, indicating that the reaction follows the Langmuir–Hinshelwood mechanism. A true rate constant k, characterizing the rate‐determining step of the reaction and which is independent on the amount of catalysts used, is obtained for the first time. Furthermore, it is found that the product adsorbes strongly on the surface of nanoparticles, thus inhibiting the reaction. The entire analysis provides a new perspective to study the catalytic mechanism and evaluate the catalytic activity of the peroxidase‐like nanoparticles. Abstract : Reaction mechanism : The kinetic modelling based on experiments reveals that the oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine with H2 O2 catalyzed by Pt nanoparticles immobilized in spherical polyelectrolyte brushes (SPB−Pt) follows the Langmuir–Hinshelwood mechanism.